2017
DOI: 10.1186/s13012-017-0665-x
|View full text |Cite
|
Sign up to set email alerts
|

Test of a workforce development intervention to expand opioid use disorder treatment pharmacotherapy prescribers: protocol for a cluster randomized trial

Abstract: BackgroundOverdoses due to non-medical use of prescription opioids and other opiates have become the leading cause of accidental deaths in the USA. Buprenorphine and extended-release naltrexone are key evidence-based pharmacotherapies available to addiction treatment providers to address opioid use disorder (OUD) and prevent overdose deaths. Treatment organizations’ efforts to provide these pharmacotherapies have, however, been stymied by limited success in recruiting providers (physicians, nurse practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Leaders of organizations indicated that traditional trainings do not address provider and clinician discomfort with MOUD. Detailing and learning collaboratives are promising strategies (Molfenter et al, 2017) to increase familiarity and comfort with clinical practice and regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Leaders of organizations indicated that traditional trainings do not address provider and clinician discomfort with MOUD. Detailing and learning collaboratives are promising strategies (Molfenter et al, 2017) to increase familiarity and comfort with clinical practice and regulations.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a cluster randomized clinical trial (RCT) focused on expanding access to medication for OUD (NCT02926482), 38 organizations in Florida, Ohio, and Wisconsin that were interested in expanding medication treatment were recruited for a 24-month study comparing two sets of implementation strategies [30]. The 38 organizations participating in the trial included 73 unique clinical sites.…”
Section: Methodsmentioning
confidence: 99%
“…255 Gaps exist in how rural and urban EM differ and it is important to further understand this topic, including the future of regional care access and effects of population migration. 161,[262][263][264][265][266][267][268] As more rural centers are closed and centralized metropolitan areas stretch their health care resources, there may be a greater need for trained EM telehealth providers. 29,74,262,265,266,269 During the consensus conference days, discussion included recommendations to broaden initial research questions to include a wider variety of health care providers in EM, including EMS, APPs, telepresenters, administrative teams, family members, and care partners.…”
Section: Rural Versus Urban Workforcementioning
confidence: 99%
“…161,[262][263][264][265][266][267][268] As more rural centers are closed and centralized metropolitan areas stretch their health care resources, there may be a greater need for trained EM telehealth providers. 29,74,262,265,266,269 During the consensus conference days, discussion included recommendations to broaden initial research questions to include a wider variety of health care providers in EM, including EMS, APPs, telepresenters, administrative teams, family members, and care partners. While another breakout group focused on education, the use of family and care partners in telehealth may require new instruction and assessments telehealth and health care in the future.…”
Section: Rural Versus Urban Workforcementioning
confidence: 99%